Fast transient thermal analysis of Fourier and non-Fourier heat conduction - Loh, J. S.; Abdul Azid, Ishak; Seetharamu, Kankanhally N.; Quadir, Ghulam Abdul (Elsevier Ltd., 2009)
Link to publisher's homepage at www.elsevier.com